Increased soil phosphorus availability induced by faba bean root exudation stimulates root growth and phosphorus uptake in neighbouring maize - Zhang, Deshan; Zhang, Chaochun; Tang, Xiaoyan; Li, Haigang; Zhang, Fusuo; Rengel, Zed; Whalley, William R; Davies, William J; Shen, Jianbo (The New phytologist, 2016)
Root growth is influenced by soil nutrients and neighbouring plants, but how these two drivers affect root interactions and regulate plant growth dynamics is poorly understood. Here, interactions between the roots of maize (Zea mays) and faba bean (Vicia faba) are characterized. Maize was grown alone (maize) or with maize (maize/maize) or faba bean (maize/faba bean) as competitors under five levels of phosphorus (P) supply, and with homogeneous or heterogeneous P distribution. Maize had longer root length and greater shoot biomass and P content when grown with faba bean than with maize. At each P supply rate, faba bean had a smaller root system than maize but greater exudation of citrate and acid phosphatase, suggesting a greater capacity to mobilize P in the rhizosphere. Heterogeneous P availability enhanced the root‐length density of maize but not faba bean. Maize root proliferation in the P‐rich patches was associated with increased shoot P uptake. Increased P availability by localized P application or by the presence of faba bean exudation stimulated root morphological plasticity and increased shoot growth in maize in the maize/faba bean mixture, suggesting that root interactions of neighbouring plants can be modified by increased P availability.